2021
DOI: 10.3390/jcm10061300
|View full text |Cite
|
Sign up to set email alerts
|

Changes in EEG Recordings in COVID-19 Patients as a Basis for More Accurate QEEG Diagnostics and EEG Neurofeedback Therapy: A Systematic Review

Abstract: Introduction and purpose: The SARS-CoV-2 virus is able to cause abnormalities in the functioning of the nervous system and induce neurological symptoms with the features of encephalopathy, disturbances of consciousness and concentration and a reduced ability to sense taste and smell as well as headaches. One of the methods of detecting these types of changes in COVID-19 patients is an electroencephalogram (EEG) test, which allows information to be obtained about the functioning of the brain as well as diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…On the contrary, phase 2 was marked by a significant difference of the CT and MM groups compared to the SC group, in particular for the Focus metric with large effect sizes, indicative of the damage to the visual system, with participants not being able to find the test visual signal. This assessment is confirmed by different studies which have found EEG abnormalities as possible consequences of neuronal damage provoked by the COVID-19 infection, as evidence of invasion of the CNS and PNS by this virus has become apparent [ 11 ]. These abnormalities have not only been reported on frontal and central changes in the EEG at rest and during high cognitive loads [ 10 , 11 ], but also with brain changes reflecting and atrophy of the crus II for a cognitive decline [ 41 ] and a possible relation with the ACE receptor [ 17 ].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…On the contrary, phase 2 was marked by a significant difference of the CT and MM groups compared to the SC group, in particular for the Focus metric with large effect sizes, indicative of the damage to the visual system, with participants not being able to find the test visual signal. This assessment is confirmed by different studies which have found EEG abnormalities as possible consequences of neuronal damage provoked by the COVID-19 infection, as evidence of invasion of the CNS and PNS by this virus has become apparent [ 11 ]. These abnormalities have not only been reported on frontal and central changes in the EEG at rest and during high cognitive loads [ 10 , 11 ], but also with brain changes reflecting and atrophy of the crus II for a cognitive decline [ 41 ] and a possible relation with the ACE receptor [ 17 ].…”
Section: Discussionsupporting
confidence: 57%
“…This assessment is confirmed by different studies which have found EEG abnormalities as possible consequences of neuronal damage provoked by the COVID-19 infection, as evidence of invasion of the CNS and PNS by this virus has become apparent [ 11 ]. These abnormalities have not only been reported on frontal and central changes in the EEG at rest and during high cognitive loads [ 10 , 11 ], but also with brain changes reflecting and atrophy of the crus II for a cognitive decline [ 41 ] and a possible relation with the ACE receptor [ 17 ]. However, some other factors and even treatment procedures (e.g., the prolonged periods of ICU treatment with long-term sedation) are also known as contributors to the impaired functioning of the brain.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Despite the potential neuropathogenesis, neuroimaging studies on patients with COVID-19 and other respiratory infections are limited. Electroencephalography of patients with COVID-19 infection have shown frontal lobe abnormalities [13,14], while positron emission tomography (PET) of these patients has identified altered glucose metabolism in several brain areas. These include hypometabolism in the bilateral parahippocampal and fusiform gyri, left insula [15], dorsolateral prefrontal cortex, bilateral frontal eye fields and right anterior cingulate cortex, as well as hypermetabolism in the left orbitofrontal cortex, right posterior parietal cortex and right thalamus [16].…”
Section: Introductionmentioning
confidence: 99%
“…Among long-term effects, the COVID-19 patients are at higher risk to develop Alzheimer’s disease (Hampshire et al 2021 ; Heneka et al 2020 ). In COVID-19 recovered patients a change in neural functions that was visible on electroencephalogram (EEG) (Kopanska et al 2021 ). The CNS neurons, if damaged due to prolonged hypoxia, may be difficult to repair (Holmes 2017 ).…”
Section: Therapeutic Considerations For Covid-19mentioning
confidence: 99%